2021
DOI: 10.1016/j.jhepr.2021.100363
|View full text |Cite|
|
Sign up to set email alerts
|

A multicenter analysis of the role of prophylactic transfusion of blood products in patients with cirrhosis and esophageal varices undergoing endoscopic band ligation

Abstract: analysis of the role of prophylactic transfusion of blood products in patients with cirrhosis and esophageal varices undergoing endoscopic band ligation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
1
18
1
Order By: Relevance
“…No differences in the frequency of post-EBL bleeding episodes were observed according to the previous administration of blood products. 186 A prospective randomised controlled trial evaluating the use of TEG to guide substitution of blood products in patients with cirrhosis undergoing elective procedures included 10 patients who underwent EBL, 6 were randomised to the TEG group while 4 received the standard of care. Although a sub-analysis in this subgroup was not done, in the whole study patients who were assigned to TEG received less blood products without differences in the frequency of bleeding episodes.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…No differences in the frequency of post-EBL bleeding episodes were observed according to the previous administration of blood products. 186 A prospective randomised controlled trial evaluating the use of TEG to guide substitution of blood products in patients with cirrhosis undergoing elective procedures included 10 patients who underwent EBL, 6 were randomised to the TEG group while 4 received the standard of care. Although a sub-analysis in this subgroup was not done, in the whole study patients who were assigned to TEG received less blood products without differences in the frequency of bleeding episodes.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Studies do not demonstrate a relationship between risk of bleeding and preendoscopic coagulation testing. [67][68][69][70] Rather, markers of disease severity and portal hypertension (model for end-stage liver disease and Child-Pugh score) may be more predictive of risk. Management is typically based on direct endoscopic measures for control and in some indications TIPS (transjugular intrahepatic portosystemic shunt).…”
Section: Reviewmentioning
confidence: 99%
“…A recent multicentre study demonstrated that administering platelets or FFP prior to endoscopic band ligation did not reduce bleeding. 70 The role of measures to support the haemostatic system in active severe bleeding remain unstudied and empirical individualised approaches are recommended.…”
Section: Reviewmentioning
confidence: 99%
“…There is also a lot of scepticism associated with FFP transfusion in these patients based on the results of the retrospective study of 244 patients by Mohanty et al [ 11 ] which reported more severe episodes of bleeding along with higher rebleed rates at day 5, longer hospital stay and higher mortality at 42 d among 100 patients with AVB who received FFP. Even for patients undergoing prophylactic EVL of varices, higher rates of post EVL bleed were associated with advanced liver disease and not baseline INR or platelets as reported by Blasi et al [ 33 ] Thus baseline thrombocytopenia or deranged INR do not lead to higher post EVL bleeding rates in a prophylactic or emergent setting and attempting to correct it with transfusions may lead to more harm than good.…”
Section: Discussionmentioning
confidence: 81%